Avaliação dos fatores e graus de risco associados ao adoecimento em contatos de Hanseníase - Edilamar Silva de Alecrin (2023)
Introduction: Leprosy is an infectious disease caused by Mycobacterium leprae, which affects the peripheral nerves and skin, with great disabling potential. Several studies identify risk factors for the illness of leprosy contacts. Factors related to the index case, social factors, epidemiological factors, immunological factors, among others, have been described. General objective: To evaluate the factors and degrees of risk associated with the illness of leprosy contacts. Methods: The systematic review was performed in compliance with the Cochrane Manual for Systematic Reviews of Interventions and the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The study protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO). Data were collected from a cohort of 600 contacts of people with leprosy assisted by the National Reference Center for Leprosy and Sanitary Dermatology of the Federal University of Uberlândia (Credesh/HC-UFU) monitored between 2002 and 2022. The database was monitored in two parts, with 2/3 to build the risk of illness score and 1/3 to validate this score. Predictive factors of leprosy adoption were used to create a disease risk score in leprosy contacts from the logistic regression model. The prediction quality was evaluated based on the construction of the Receiver Operating Characteristic Curve (ROC) and the calculation of the Area under the Curve (AUC). Measures of diagnostic quality, sensitivity and specificity, positive and negative predictive values, in addition to the overall accuracy of the models were considered. Results: The systematic review identified the following risk factors associated with the development of leprosy in Brazilian contacts: seropositivity for anti-phenolic glycolipid antibodies (anti-PGL-I); negative Mitsuda test; absence of Bacillus Calmette-Guérin scar (BCG-ID); positive quantitative polymerase chain reaction (qPCR) in blood; being a child or elderly person; brown/black race; be a spouse; be a blood relative; have a low level of education; have contact time greater than five years; be household contact, as well as elements related to the index case (bacilloscopic index; genetic conditions, family relationships). Some combined factors were also identified, mainly anti-PGL-I IgM serology; Mitsuda test and BCG-ID scar. Of the four models constructed, model 3, which contains the variables anti-PGL-I positive IgM, absence of BCG vaccine scar and age ≥60 years, was considered the best for identifying a higher risk of illness, with a specificity of 89.2%. positive predictive value of 60% and accuracy of 78%. Conclusion: Model 3 was considered the best model to predict the illness of leprosy contacts in Brazil. The development of models for predicting the risk of illness in leprosy contacts can help guide the management of leprosy contacts and systematize contact assessment protocols. To this end, it is suggested that further studies be carried out in other groups of contacts to better assess its applicability and impact on disease control, surveillance and contact management.